ANALISIS ALOKASI DANA DESA DI KEBUPATEN LEBONG TAHUN 2016 - Nosy Mayasari; Abdullah Abdullah (Jurnal Akuntansi, 2018)
This study aims to analyze whether the procedure of allocation of Village Funds in Lebong Regency has been in accordance or not in accordance with Regulation of the Minister of Finance RI No.49 of 2016 on Procedure of Allocation of Village Funds. This research uses descriptive research approach. The data used in this study is secondary data, in the form of Lebong Village Fund (DD) data issued by Minister of Finance Regulation No. 49 of 2016, population, area, poverty rate, and geographical difficulties index. The object of research in this study as many as 12 District in Lebong District. The results of the research analysis indicate that the procedures for allocating village funds have followed the guidelines of the applicable rules, but the data used in the calculation of Village Fund Allocation are not all sourced from the Central Bureau of Statistics of Lebong Regency while in the Minister of Finance Regulation No.49 of 2016 Data must be sourced from the statistics field.Key words: Village Fund Allocation